Physiological and psychological effects of a 12-week home-based telemonitored training in metabolic syndrome - Máthéné Köteles, Éva; Rafael, Beatrix; Korom, Andrea; Vágvölgyi, Anna; Ábrahám, Judit Erzsébet; Domján, Andrea; Szűcs, Mónika; Nemes, Attila; Barnai, Mária; Lengyel, Csaba; Kósa, István (Frontiers in Cardiovascular Medicine, 2023)
Background Metabolic Syndrome (MetS) increases the risk of cardiovascular diseases (CVD) and affects around one fourth of the population worldwide. In the prevention and treatment regular exercise trainings are inevitable. Providing personal supervision in out/inpatient care settings for such a large target population challenges the healthcare systems, but using telemonitoring of the home-performed trainings could be a promising and widely available option. Objectives The aim of this study was to evaluate the physiological and psychological effects of a 12-week home-based physical training program, telemonitored by widely available fitness devices on parameters of MetS patients. Methods A total of 55 MetS patients (mean age 49.19 ± 7.93 years) were involved in the study. They were asked to perform 3–5 sessions of exercise activity (min. 150 min) each week for 12 weeks. Trainings were monitored off-line by heart rate sensors, a fitness application and a cloud-based data transfer system. Physiotherapists supervised, coached, and feedback the trainings through an online coach system. We investigated different anthropometric parameters, maximum exercise and functional capacity levels, laboratory parameters, the level of depression, insomnia, vital exhaustion, and wellbeing as well. Results The average weekly training time was 152.0 ± 116.2 min. Out of the 55 participants who completed the program, 22 patients (40%) performed the recommended 150 min or more weekly. Patients showed statistically significant changes in: all the measured waist and hip circumferences; 6-min walk distance (6MWD; from 539.69 ± 78.62 to 569.72 ± 79.96 m, p < 0.001); maximal exercise capacity (11.02 ± 2.6 to 12.14 ± 2 MET, p < 0.001), stress-electrocardiogram duration time (13.74 ± 3.29 to 15.66 ± 2.64 min, p < 0.001); body weight (98.72 ± 21.7 to 97.45 ± 21.76 kg, p = 0.004); high-density lipoprotein cholesterol (n = 45, 1.28 ± 0.31 to 1.68 ± 0.36 mmol/L, p < 0.001); fasting plasma glucose (FPG; n = 47, 6.16 ± 1.26 to 5.44 ± 1.31 mmol/L, p = 0.001); glycated hemoglobin A1c (HbA1c; n = 41, 6.22 ± 0.68 to 5.87 ± 0.78%, p = 0.01). Out of the 55 patients who finished the program 38 patients (70%) completed all the psychological questionnaires. We found statistically significant decrease of the overall scores of the Maastricht Vital Exhaustion Questionnaire, from 3.37 ± 2.97 points to 2.63 ± 2.70 points (p < 0.05) and a significant increase of the overall scores of the WHO Wellbeing Scale from 9.92 ± 2.59 points to 10.61 ± 2.76 points (p < 0.05). We have not found any statistically significant changes in the scores of the Beck Depression Inventory and the Athens Insomnia Scale. Conclusion A 12-week home-based telemonitored training supported by an affordable, commonly available device system produces positive, statistically significant changes in many core components in MetS patients. Telemonitoring is a cheap method for coaching and feeding back the home-based interventions.